Novelties in Vietnamese Craibiodendron, Lyonia and Vaccinium (Ericaceae) - Tong, Yihua; Fritsch, Peter W.; Huong, Nguyen Thi Thanh; Averyanov, Leonid V.; Kuznetsov, Andrey N.; Kuznetsova, Svetlana P.; Nuraliev, Maxim S. (Phytotaxa, 2022)
The paper summarizes the knowledge on three Vietnamese species of Ericaceae. Craibiodendron yunnanense is newly documented for the flora of Vietnam. The presence of Lyonia villosa in the country is confirmed by specimen citation. We publish a new combination, Vaccinium glaucorubrum, to accommodate the taxon earlier known as Vaccinium gaultheriifolium var. glaucorubrum at species rank. We provide a detailed morphological description of V. glaucorubrum and revise the geographical distribution of this species. We review type material of V. glaucorubrum and designate the specimen at KUN (1208884) as a lectotype. We illustrate all three species with analytical photographs of the plants in the living state.